On Immigration and Native Entrepreneurship - Harriet Duleep; David A. Jaeger; Peter McHenry (Institute of Labor Economics (IZA), 2021)
We present a novel theory that immigrants facilitate innovation and entrepreneurship by being willing and able to invest in new skills. Immigrants whose human capital is not immediately transferable to the host country face lower opportunity costs of investing in new skills or methods and will be more exible in their human capital investments than observationally equivalent natives. Areas with large numbers of immigrants may therefore lead to more entrepreneurship and innovation, even among natives. We provide empirical evidence from the United States that is consistent with the theory's predictions.
Keywords: J15; J24; J39; J61; L26; 330; immigration; innovation; entrepreneurship; human capital